ANALYSIS ON NANO DRUG DELIVERY SYSTEMS ON CARDIOVASCULAR DISEAS TREATEMENT - K.SUMANGALI, SK.JANBEE, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nanomedicine and nano-delivery systems is a new but rapidly developing science in which nanomedicine materials are used as diagnostic tools or in a controlled manner to provide therapeutic compounds in specific target areas. In the treatment of chronic human disease via location-specific and targeted administration of accurate medications, nanotechnology has many advantages. In recent times a lot of excellent applications of nanomedicine in the treatment of various diseases have been made (chemotherapy agents, biological agents, immunotherapy agents etc.). The hazard to human life and health has been seriously impacted by cardiovascular diseases (CVDs). Although several medicines operating under multiple action mechanisms are available on the market as conventional CVD formulations, their low water solubility and limited biological activity, non-targeting, and drug resistance still make them far from adequate. New methods of delivery of CVDs through the creation of nanotechnology for drug delivery systems (NDDS) demonstrate considerable benefits in the resolution of the foregoing challenges. Nano-drug delivery systems major aim is to study the recent progress in cardiovascular medication carriers based on nanoparticles. In this work, the problems of the conventional treatment methods compared with the nanomedicine of CVDs are summarised.